Randomized two dimensional between patient response surface pathway design with two interventional and one response variable in estimating minimum efficacy dose - Larsen, Stig; Holand, Trond; Bjørnæs, Kjell; Glomsrød, Espen; Kaufmann, Joachim; Garberg, Tor Harald; Elvbakken, Geir; Dalhøi, Bård; Reiertsen, Ola; Dewi, Sagita (International Journal of Clinical Trials, 2019)
Background: The aim of this paper is to introduce and evaluate the RSP design with two interventional and one response variable exemplified by estimating minimum efficacy dose (MED) of osteopathic manual therapy (OMT) in treatment of gastroesophageal reflux disease (GERD). Methods: 15 GERD patients, divided in three design-level with three, five and seven patients. The study was performed as a randomized two-dimensional, between-patient RSP designed multicenter study with two interventional– and one response variable. The interventional variables “Number of OMT’s” and “Treatment Interval” with common response variable, formed two independent one-dimensional randomized between-patient RSP studies. The response variable was percent reduction in sum of the five GERD score from baseline. Three GERD patients were allocated on the first design level and given six OMT with five days’ interval. Based on results obtained in the first and second design level, five patients were included to the second design level and seven to the third. Results: The two-dimensional randomized between-patient RSP-design with the combined outcome procedure worked as expected. The percent reduction in GERD score increased with increasing number of OMT’s and time intervals. This increase leveled out after three to five OMT’s and three to four days between treatments. A clinical interaction between the two interventional variables was obtained. The estimated MED of OMT in treatment of GERD was three treatments with two days between treatments. Conclusions: The suggested two-dimensional, randomized between-patient RSP-design worked as expected and estimated MED of OMT in GERD patient sufficiently.